Faktor-Faktor yang Berhubungan dengan Gangguan Fungsi Paru pada Pekerja Pengelasan Di Kota Pontianak - Slamet Slamet; Laila Kamila (Jurnal Laboratorium Khatulistiwa, 2017)
Abstract: Â One of the wastes material from the welding process is particulate that has exposure potential to workers. This study was aimed to measure pulmonary function disorders on welding workers and factors inï¬‚uencing it in Pontianak City. This research was an observational research using cross-sectional design, with 78 samples of worker were taken by random sampling. Data of respirable welding dust levels were obtained by measurement using personal dust sampler, while pulmonary function disorder data obtained by examining the pulmonary function of workers using spirometry, and other data obtained by interview. Data analyzed by univariate and bivariate analysis with Kendall-tau and chi-square (Î± = 0,05). Result of study showed that respirable dust still below threshold limit value (TLV = 3 mg/m3), the highest = 2,791 mg/m3, the lowest = 0,085 mg/m3, mean = 0,83 mg/m3 and SD = 0,70, and 59 respondents (75.6%) had pulmonary function disorders. Statistical test results showed there was significant association between level of respirable dust (p-value = 0,001), and working hour/day (p-value = 0,008, OR = 6,321, 95%CI = 1,663-24,026 with pulmonary function disorders. Conclusion of this study was respirable dust level and duration of exposure were potential factors of pulmonary function disorders in welding workers in Pontianak City.Abstrak: Salah satu bahan buangan dari proses pengelasan adalah partikulat yang berpotensi menimbulkan paparan pada pekerjanya. Tujuan dari penelitian ini yaitu untuk mengukur gangguan fungsi paru pada pekerja pengelasan dan faktor-faktor yang mempengaruhinya di Kota Pontianak. Penelitian ini merupakan penelitian observasional dengan pendekatan cross sectional, dengan jumlah sampel 78 pekerja diambil secara random sampling. Data kadar debu las terhirup diukur menggunakan personal dust sampler, sedangkan data fungsi paru pekerja diukur menggunakan spirometri, dan untuk data lain diperoleh melalui wawancara. Analisis data dilakukan secara univariat, bivariat menggunakan uji Kendall-tau dan Chi-square (Î± = 0,05). Hasil penelitian menunjukkan kadar debu terhirup masih dibawah Nilai Ambang Batas (NAB = 3 mg/m3), tertinggi = 2,791 mg/m3, terendah = 0,085 mg/m3, rata-rata = 0,83 mg/m3 dengan standar deviasi 0,70 dan sebanyak 59 responden (75,6%) mengalami gangguan fungsi paru. Hasil uji statistik menunjukkan ada hubungan yang bermakna antara kadar debuterhirup (p-value = 0,001) dan lama paparan (p-value = 0,008, OR = 6,321, 95%CI = 1,663-24,026) dengan gangguan fungsi paru. Kesimpulan dari penelitian ini adalah kadar debu terhirup dan lama paparan merupakan faktor potensial terjadinya gangguan fungsi paru pada pekerja pengelasan di Kota Pontianak.